2021
DOI: 10.2147/idr.s331040
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, Risk Factors, and Antimicrobial Susceptibility Test of Thermophilic Campylobacter Species of Bovine Carcass at Municipal Abattoir and Butcher Shops of Jimma Town, Southwest Ethiopia

Abstract: Background Although Campylobacter jejuni ( C. jejuni ) and Campylobacter coli ( C. coli ) cause acute diarrheal diseases in people all over the world, they are most commonly seen in other mammalian species and are a seemingly healthy carrier condition. Humans in Ethiopia, on the other hand, are largely unaware of the existence of Campylobacter in food animals as po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
(45 reference statements)
3
4
0
Order By: Relevance
“…The prevalences of C. jejuni (72%) and C. coli (28%) in this study are in agreement with those of Berhanu et al [10] who reported 78.6% C. jejuni and 21.4% C. coli. Similarly, Hagos et al [22] reported C. jejuni and C. coli incidences of 81.25% and 18.75%, respectively, which is consistent with the ndings of the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The prevalences of C. jejuni (72%) and C. coli (28%) in this study are in agreement with those of Berhanu et al [10] who reported 78.6% C. jejuni and 21.4% C. coli. Similarly, Hagos et al [22] reported C. jejuni and C. coli incidences of 81.25% and 18.75%, respectively, which is consistent with the ndings of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the total prevalence of Campylobacter species was relatively in agreement with that reported by Tegegne et al [12], who reported a 5% prevalence of Campylobacter species in camel meat samples from Jigjiga town. Berhanu et al [10] and Debelo et al [21] from the Jimma municipal abattoir also reported overall prevalence rates of 5.6% and 7.9%, respectively, which are in agreement with the ndings of the present study. In contrast, Chala et al [11] from Addis Ababa and Hagos et al [22] from Mekele reported relatively more Campylobacter isolates from different sample sources, with a prevalence of 18.5% and 16.67%, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of Campylobacter spp. at slaughterhouse is approximately 20% (ranged from 5% to 40%) in cattle [ 189 , 190 , 191 , 192 , 193 , 194 , 195 ].…”
Section: Surveillance Of Zoonotic Agents In the Slaughterhousementioning
confidence: 99%
“…Using the toilet, handling meat without washing your hands, handling meat after it has been in contact with dirt during preparation are four situations when campylobacter is more likely to be present. Meat handlers who did not wash their hands before handling the meat had 11.6 times higher risk of contracting Campylobacter spp (Berhanu et al, 2021). Lack of hygienic practices (Sibanda et al, 2018), depopulation of a flock in several batches, the presence of other farm animals and pets (Sanches et al, 2018), the presence of multiple poultry houses, the presence of rodents on a farm, the use of nipples drinkers, the enormous size of the flock (Sibanda et al, 2018), receiving chicks from the individual hatchery, and increasing ventilation are all factors that contribute to poultry colonization during summer (Hog et al, 2016), and lack of fly screen .…”
Section: Risk Factorsmentioning
confidence: 99%